Country-of-origin-specific economic capital in neighbourhoods: Impact on immigrants' employment opportunities. (August 2021) - Kadarik, Kati; Miltenburg, Emily; Musterd, Sako; Östh, John
Does living in an area characterized by high concentrations of residents of the same country-of-origin deprive ethnic minority groups, or does potential access to an extended country-of-origin-specific network stimulate their integration? This paper takes a new approach to analysing the potential of country-of-origin-specific economic capital in neighbourhoods to increase employment opportunities. We add to the 'ethnic enclave' debate by measuring country-of-origin-specific economic capital as the rate of employed co-countrymen, while controlling for the presence of co-countrymen and general employment rates in the neighbourhood. Whereas many studies employ aggregated data to estimate the impact of neighbourhood, here we use individualized, scalable neighbourhoods. This allows for a flexible approach in studying the impact of country-of-origin-specific economic capital in neighbourhoods. We employ individual longitudinal Swedish registry data for 2000–2010 on working-age individuals of Iraqi, Iranian, Turkish, and Somalian backgrounds in Stockholm, Göteborg, and Malmö. We find that an increased share of employed co-countrymen positively influences individual employment prospects. We add to existing knowledge by showing that the impact of minority clustering on employment outcomes is conditional on the quality of local networks – i.e., country-of-origin-specific economic capital – and on the scale of measurement.